Substance use care innovations during COVID-19: barriers and facilitators to the provision of safer supply at a toronto COVID-19 isolation and recovery site - Gillian Kolla; Chowdhury Nishwara Tarannum; Kaitlin Fajber; Fiqir Worku; Kris Norris; Cathy Long; Raphaela Fagundes; Anne Rucchetto; Eileen Hannan; Richard Kikot; Michelle Klaiman; Michelle Firestone; et al. (BMC, 2024)
Abstract Background Early in the COVID-19 pandemic, there was an urgent need to establish isolation spaces for people experiencing homelessness who were exposed to or had COVID-19. In response, community agencies and the City of Toronto opened COVID-19 isolation and recovery sites (CIRS) in March 2020. We sought to examine the provision of comprehensive substance use services offered to clients on-site to facilitate isolation, particularly the uptake of safer supply prescribing (prescription of pharmaceutical opioids and/or stimulants) as part of a spectrum of comprehensive harm reduction and addiction treatment interventions. Methods We conducted in-depth, semi-structured interviews with 25 clients and 25 staff (including peer, harm reduction, nursing and medical team members) from the CIRS in April-July 2021. Iterative and thematic analytic methods were used to identify key themes that emerged in the interview discussions. Results At the time of implementation of the CIRS, the provision of a safer supply of opioids and stimulants was a novel and somewhat controversial practice. Prescribed safer supply was integrated to address the high risk of overdose among clients needing to isolate due to COVID-19. The impact of responding to on-site overdoses and presence of harm reduction and peer teams helped clinical staff overcome hesitation to prescribing safer supply. Site-specific clinical guidance and substance use specialist consults were crucial tools in building capacity to provide safer supply. Staff members had varied perspectives on what constitutes 'evidence-based' practice in a rapidly changing, crisis situation. Conclusion The urgency involved in intervening during a crisis enabled the adoption of prescribed safer supply, meeting the needs of people who use substances and assisting them to complete isolation periods, while also expanding what constitutes acceptable goals in the care of people who use drugs to include harm reduction approaches.